VASCULAR EFFECTS OF ANTI-CANCER CISPLATIN THERAPY. (June 2018) - Cameron, Alan C.; Hall, M.; Rios, F.; Waterston, A.; White, J.; Touyz, R.M.; Lang, N.N.
Abstract : Objective: Cisplatin-containing chemotherapy is an effective cure for the majority of men with testicular cancer. However, patients treated with cisplatin are at increased risk of cardiovascular events. It is not clear whether this reflects primarily early direct vascular toxicity, or a latent pro- atherogenic state. We hypothesised that cisplatin-containing chemotherapy induces acute endothelial injury and a prothrombotic state. Design and method: We conducted a prospective study of patients with testicular cancer who attended the Beatson West of Scotland Cancer Centre. Patients were recruited into 3 groups according to management: (1) surveillance, (2) 1–2 cycles of adjuvant cisplatin-containing chemotherapy (3) 3–4 cycles of curative cisplatin-containing chemotherapy. Patients attended 6 visits over 9 months, each visit including an assessment of endothelial function by % flow-mediated dilatation (FMD) and collection of venous blood for analysis. Visit 1 was < 8 weeks following orchidectomy, visit 2 was < 24 hours after initial cisplatin cycle and subsequent visits were at 6 weeks, 3 months, 6 months and 9 months. Results: 26 patients were recruited between January 2016 and August 2017. 9 patients were managed with surveillance, 7 received 1-2 cycles of cisplatin and 10 received 3–4 cycles of cisplatin. In all patients receiving cisplatin, % FMD reduced from 15.0 ± 1.2 to 10.8 ± 0.7 within 24 hours (p = 0.01). On subsequent visits, % FMD was not significantly different from baseline. Serum cholesterol increased from 5.5 ± 0.2 to 7.2 ± 0.5 mmol/L at 6 weeks after receiving 3–4 cycles of cisplatin (p = 0.01). There was a trend to increasing serum triglycerides after cisplatin-containing chemotherapy. Conclusions: Cisplatin-containing chemotherapy is associated with acute endothelial toxicity that recovers within 6 weeks, hypercholesterolaemia and a trend to hypertriglyceridaemia. Our observations may explain some of the early pro-thrombotic effects of cisplatin. These data should help define therapeutic strategies to prevent short- and long-term adverse vascular effects of cisplatin-containing chemotherapy.